2021
DOI: 10.2147/ott.s289241
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circDNM3OS Functions as a miR-145-5p Sponge to Accelerate Cholangiocarcinoma Growth and Glutamine Metabolism by Upregulating MORC2

Abstract: Background Cholangiocarcinoma (CCA) is the second most common liver malignant tumor. CircRNA hsa_circ_0005230 (circDNM3OS) has been reported to exert an oncogenic role in CCA. However, the mechanisms related to circDNM3OS in CAA progression have not been fully elucidated. Methods The expression of circDNM3OS, microRNA (miR)-145-5p, and MORC2 (MORC Family CW-Type Zinc Finger 2) mRNA were analyzed by quantitative real-time polymerase chain reaction (qRT-PCR). Cell prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…For example, a perturbation of MORC2 localization disrupts adipocyte homeostasis in mice (Hallenborg et al, 2021), leading to an increase in adipose tissue mass, glucose intolerance and hepatic steatosis in young mice. On the other hand, an increase in MORC2 expression promotes the growth of cholangiocarcinoma associated with increased glutamine metabolism (Su et al, 2021).…”
Section: Metabolismmentioning
confidence: 99%
“…For example, a perturbation of MORC2 localization disrupts adipocyte homeostasis in mice (Hallenborg et al, 2021), leading to an increase in adipose tissue mass, glucose intolerance and hepatic steatosis in young mice. On the other hand, an increase in MORC2 expression promotes the growth of cholangiocarcinoma associated with increased glutamine metabolism (Su et al, 2021).…”
Section: Metabolismmentioning
confidence: 99%
“… Prevalence of genomic aberrations by anatomic classification in cholangiocarcinoma [ 91 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 ]. …”
Section: Future Directionsmentioning
confidence: 99%
“…circ-CCAC1 sponges miR-514a, which regulates YY1 expression, and high levels of circ-CCAC1 in circulating EVs promoted CCA growth and metastases in xenograft mouse models [99]. A study using 35 paired CCA tissues and adjacent normal tissues identified elevated expression of circ-DNM3OS associated with TNM stage and lymph node invasion in CCA patients [100]. circ-DNM3OS induces MORC family CW-type zinc finger 2 (MORC2) expression via sponging miR-145, and inhibition of circ-DNM3OS decreased tumor growth by upregulation of miR-145 and downregulation of MORC2 in xenograft mice [100].…”
Section: Biomarkersmentioning
confidence: 99%